Philosophy and the Mirror of Nature - Rorty, Richard 1931-2007 (Princeton Classics, 2018)
When it first appeared in 1979, Philosophy and the Mirror of Nature hit the philosophical world like a bombshell. In it, Richard Rorty argued that, beginning in the seventeenth century, philosophers developed an unhealthy obsession with the notion of representation: comparing the mind to a mirror that reflects reality. Rorty's book is a powerful critique of this imagery and the tradition of thought that it spawned. Today, the book remains a must-read and stands as a classic of twentieth-century philosophy. Its influence on the academy, both within philosophy and across a wide array of disciplines, continues unabated. This edition includes new essays by philosopher Michael Williams and literary scholar David Bromwich, as well as Rorty's previously unpublished essay "The Philosopher as Expert."